Livestock and deforestation in Central America in the 1980s and 1990s: a policy perspective - Kaimowitz, D. (1996)
This study analyses seven factors used to explain the conversion of forest to pasture in Central America between 1979 and 1994: 1) favourable markets for livestock products; 2) subsidised credit and road construction; 3) land-tenure policies; 4) limited technological change in livestock production; 5) policies which reduce timber values; 6) reduced levels of political violence; and 7) characteristics specific to cattle which make conversion attractive. Deforestation rates in Central America declined in the 1980s, but remained high. After expanding rapidly, cattle population and pasture area have stagnated, although they continue to expand on the humid tropical frontier. Strong markets for beef and dairy products stimulated livestock expansion and deforestation in the 1960s and 1970s after which markets for livestock products became less favourable, which led to lower investment. During the 1960s and 1970s large government subsidies for cattle raising encouraged forest conversion. Since then credit subsidies have been reduced, but subsidised public road construction continues, causing widespread deforestation. Land speculation is another reason why pasture expansion has continued in agricultural frontier areas. There is little evidence that technological progress in livestock production reduces deforestation. Nor is it clear that removing policies which discriminate against forest production would have a major positive effect in this regard. The author proposes: 1) restrictions on road construction and livestock credit in agricultural frontier areas; 2) increased enforcement of land-use restrictions in protected areas; 3) the expansion of land rights for indigenous peoples; 4) stronger restrictions on the titling of natural lands by large landholders; 5) pilot efforts to establish local land taxes with higher rates for pasture and crop lands than for forest; and 6) economic incentives for secondary forest regeneration and research on pasture degradation in Central America.